The Abdominal Hernia-Q: Development, Psychometric Evaluation, and Prospective Testing. Issue 5 (May 2020) - Mauch, Jaclyn T.; Enriquez, Fabiola A.; Shea, Judy A.; Barg, Frances K.; Rhemtulla, Irfan A.; Broach, Robyn B.; Thrippleton, Sheri L.; Fischer, John P.
Abstract : Objective: Our study completes the development and estimates the psychometric properties of a novel, ventral hernia-specific patient reported outcomes (PRO) tool—the Abdominal Hernia-Q (AHQ). Summary Background Data: A standardized method for measuring hernia-related PRO has not been identified. There remains a need for a broadly applicable, hernia-specific tool that incorporates patient viewpoints and offers pre- and postoperative forms. Methods: Concept elicitation interviews, focus groups, and cognitive debriefing interviews were completed to define content. The preoperative AHQ was administered to patients scheduled to have a ventral hernia repair (VHR). The postoperative AHQ was administered to patients within 24 months post-VHR. The SF-12 and HerQLes were concurrently administered. Psychometric evaluation was performed. Subsequently, the AHQ (pre: 8 items; post: 16 items) underwent prospective testing. Results: Cross-sectional evaluations of patient responses to the AHQ (pre n = 104; post n = 261) demonstrated high internal consistency (Cronbach α pre = 0.86; post = 0.90) and moderate disattenuated correlations with the HerQLes (pre r = —0.71 and post r = —0.70) and the SF-12 domains (pre and post r ≥ 0.5 for 7 of 8 domains). Principal components analyses produced 2 factors preoperatively and 3 factors postoperatively. In prospective testing (n = 67), the AHQ scores replicated the cross-sectional psychometric results and suggested sensitivity to clinical outcomes. Conclusions: Through patient involvement and rigorous, iterative psychometric evaluation, we have produced substantial data to suggest the validity and reliability of AHQ scores in measuring hernia-specific PRO. The AHQ advances the clinical management and treatment of patients with abdominal hernias by providing a more complete understanding of patient-defined outcomes. Abstract : Supplemental Digital Content is available in the text